2012
DOI: 10.1093/mp/ssr114
|View full text |Cite
|
Sign up to set email alerts
|

Drought Responses of Leaf Tissues from Wheat Cultivars of Differing Drought Tolerance at the Metabolite Level

Abstract: Drought has serious effects on the physiology of cereal crops. At the cellular and specifically the metabolite level, many individual compounds are increased to provide osmoprotective functions, prevent the dissociation of enzymes, and to decrease the number of reactive oxygen species present in the cell. We have used a targeted GC-MS approach to identify compounds that differ in three different cultivars of bread wheat characterized by different levels of tolerance to drought under drought stress (Kukri, into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
326
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(367 citation statements)
references
References 64 publications
37
326
2
2
Order By: Relevance
“…D1 protein, which is encoded by psbA gene, is an important structural and functional component in Photosystem (PS) II complexes [25]. It is reported that psbA gene transcription level decreases significantly in wheat seedling under drought stress [26].…”
Section: Discussionmentioning
confidence: 99%
“…D1 protein, which is encoded by psbA gene, is an important structural and functional component in Photosystem (PS) II complexes [25]. It is reported that psbA gene transcription level decreases significantly in wheat seedling under drought stress [26].…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress, which has been identified as the most devastating abiotic constraint on crop productivity (Francia et al, 2005;Reynolds et al, 2005), causes substantial perturbations in plant metabolism (Bowne et al, 2011(Bowne et al, , 2012. Previous QTL studies of agronomic traits in wheat have lacked information on the biochemical pathways underlying those traits and their responses to drought.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that metabolic and proteomic profiles of cv Excalibur differ from those of cv Kukri following cyclic drought (Ford et al, 2011;Bowne et al, 2012). Thus, it should be possible to use progeny from a cv Excalibur/Kukri cross to map QTLs affecting the levels of individual metabolites under drought stress conditions.…”
mentioning
confidence: 99%
“…Under drought, the quantity of proteins usually declines, while free amino acids tend to accumulate being partially converted into compatible solutes (e.g., proline) as reported by several groups during the past decades (Yoshiba et al, 1997;Su and Wu, 2004;Gruszka Vendruscolo et al, 2007;Parida et al, 2008;Bowne et al, 2012). Proline accumulation under abiotic stresses was reviewed in detail by Verbruggen and Hermans (2008).…”
Section: Nitrogen Metabolismmentioning
confidence: 98%
“…Sink capacities may be strongly reduced under drought and heat. This may lead to an abnormal type of senescence accompanied by accumulation of free amino acids which could be partially converted into osmoprotectants in source leaves (Bowne et al, 2012). This process is initially reversible, but when prolonged it may turn into senescence finally leading to organ death.…”
Section: Leaf Survival and Altered Timing Of Senescencementioning
confidence: 99%